Primary ovarian peripheral primitive neuroectodermal tumor presented with breast metastasis; Case report - Razan Rabi; Majd Hamed Allah; Yusuf Dawabsheh (Rare Tumors)
Ewing sarcoma family tumors (ESFT) pose diagnostic challenges, which largely depend on the primary site of involvement and tumor stage. Despite advancements in treatment, metastatic ESFTs remain associated with poor outcomes. This case describes a 21-year-old woman who, in July 2022, presented with a left breast mass identified through ultrasound and CT scan, along with abdominal distention. A biopsy of the breast mass confirmed metastatic extraskeletal Ewing sarcoma. Further imaging revealed an ovarian mass, with subsequent biopsy confirming ovarian origin as extraskeletal Ewing sarcoma. The breast mass was identified as metastatic based on imaging features, including irregular margins and CT scan confirmation of widespread metastasis. Histopathology and immunohistochemistry confirmed Ewing sarcoma, consistent with the ovarian mass pathology that was the primary site. She underwent 15 cycles of VDC/IE chemotherapy ((vincristine, doxorubicin, and cyclophosphamide) for 2 days and 5 days IE (ifosfamide etoposide)), resulting in tumor cytoreduction. However, in less than 2 years, she developed metastases to the dura, spine, and bone, with optic nerve involvement. Despite treatment with radiotherapy and two cycles of high-dose Ifosfamide chemotherapy, her condition deteriorated, and she passed away in April 2024. This case underscores the complexity of managing metastatic ESFTs. Further research is needed to improve outcomes and establish treatment protocols for this malignancy.